Bevameter testing on simulant Fillite for planetary rover mobility applications. (April 2017) - Edwards, Michael B.; Dewoolkar, Mandar M.; Huston, Dryver R.; Creager, Colin
Highlights: Fillite is capable of simulating high-sinkage, high-slip situations for rovers on Earth. Bevameter testing proved effective in examining pressure-sinkage and shear behavior of Fillite. Estimated wheel sinkage in Fillite compared reasonably well with the entrenchment of Spirit rover on Mars. Estimated shear in Fillite compared reasonably well to the Spirit rover wheels in Martian soil. Fillite facilitates more suitable sinkage and shear behavior than terrestrial soil-based simulants (e.g. GRC-1). Abstract: This paper examines pressure-sinkage and shearing behavior via bevameter testing of a light-weight, granular simulant called Fillite in support of laboratory modeling of rover mobility in high-sinkage, high-slip environments typically found on Mars, the Moon, and other planetary bodies. Normal bevameter test results helped to determine parameters for the Bekker model, the New Model of Mobility (N2M) sinkage model, and the Bekker-Wong model. A case study used the Bekker-Wong model parameters to predict the possible sinkage of 84% into Fillite of a wheel on the Mars Spirit rover, a value within the observed sinkage of 50–90% of the wheel diameter of the Spirit rover on Mars. Shear bevameter testing of Fillite provided a second set of parameters to assess shear behavior, this time simulating the stresses and shear deformations imparted by rotating wheels. The results compared well to the estimated shear stresses and deformations of Martian soil caused by the wheels of the Spirit rover. When compared to other simulants (e.g. GRC-1), the results confirm that Fillite is possibly more suitable for high-sinkage and high-slip rover studies than other typical simulants derived from natural terrestrial soils and rocks.